(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Present study is concerned the influence of chemical reaction on Magneto Hydro Dynamics (MHD) flow on continuously moving vertical surface with uniform heat and mass flux taking into account the ho mogeneous chemical reaction of 1st order. The expressions for velocity, temperature, concentration and skin friction are obtained. The effects of various parameters are discussed with the help of graphs and table.